2004
DOI: 10.1136/ard.2003.011205
|View full text |Cite
|
Sign up to set email alerts
|

Autologous stem cell transplantation in the treatment of systemic sclerosis: report from the EBMT/EULAR Registry

Abstract: Objective: To analyse the durability of the responses after haematopoietic stem cell transplantation (HSCT) for severe systemic sclerosis (SSc) and determine whether the high transplant related mortality (TRM) improved with experience. This EBMT/EULAR report describes the longer outcome of patients originally described in addition to newly recruited cases. Methods: Only patients with SSc, treated by HSCT in European phase I-II studies from 1996 up to 2002, with more than 6 months of follow up were included. Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
130
1
26

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 235 publications
(159 citation statements)
references
References 47 publications
2
130
1
26
Order By: Relevance
“…Improved skin score and quality of life and at least stabilization of lung function were consistently reported in early phase II trials. [4][5][6][7][8] Recently, the phase II ASSIST 9 and the larger phase III ASTIS 10 prospective randomized trials showed better survival rates and improved skin, lung and functional status in patients treated with AHSCT as compared with monthly IV cyclophosphamide. Still, the transplant-related mortality reaching 10% and disease-progression rates of around 20-30% after AHSCT indicate that further improvements are still warranted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improved skin score and quality of life and at least stabilization of lung function were consistently reported in early phase II trials. [4][5][6][7][8] Recently, the phase II ASSIST 9 and the larger phase III ASTIS 10 prospective randomized trials showed better survival rates and improved skin, lung and functional status in patients treated with AHSCT as compared with monthly IV cyclophosphamide. Still, the transplant-related mortality reaching 10% and disease-progression rates of around 20-30% after AHSCT indicate that further improvements are still warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Still, the transplant-related mortality reaching 10% and disease-progression rates of around 20-30% after AHSCT indicate that further improvements are still warranted. [6][7][8][9][10][11][12] Among current strategies to increase safety and efficacy of AHSCT, the benefit of ex vivo CD34+ positive selection of the graft remains debated. This study was therefore designed to evaluate the influence of ex vivo CD34+ selection on the outcome of SSc patients treated with AHSCT.…”
Section: Introductionmentioning
confidence: 99%
“…This finding might be explained by the multisystemic nature of these diseases. In recent years, TRM was lower than reported in the early years (e.g., TRM of HSCT for SSc, the second most common indication for HSCT in ADs, was as high as 16% (6) before 2001, and in a later analysis TRM for patients with the same disease was 8.5%) (7). The reduction of TRM has been attributed to better patient selection and to adaption of conditioning regimens.…”
Section: Trmmentioning
confidence: 89%
“…Marked improvement of high skin scores and lung function has been observed. 46 Concepts of irreversible tissue damage during the fibrotic process need to be revised. In immune thrombocytopenia, bleeding remains a major concern and was associated with the death of two patients.…”
Section: Discussionmentioning
confidence: 99%